(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The article analyzes the contribution of the Federal Supreme Court (STF) to the recognition and strengthening of freedom of artistic expression in Brazilian democracy. It is based on the assumption that the STF, in the exercise of judicial review, plays an essential role in safeguarding the essential conditions for the free exercise of artistic expression in the political, economic and social scenario. Based on doctrine and legislation on the subject, paradigmatic decisions of the STF on the subject are analyzed, with the aim of presenting the state of the art in the 35 years of the Constitution.